Advances in Design for Inclusion Proceedings of the AHFE 2016 International Conference on Design for Inclusion, July 27-31, 2016, Walt Disney World®, Florida, USA - Di Bucchianico, Giuseppe; Kercher, Pete (Advances in Intelligent Systems and Computing, 2016)
This book focuses on a range of topics in design, such as universal design, design for all, digital inclusion, universal usability, and accessibility of technologies independently of people's age, economic situation, education, geographic location, culture and language. It especially focuses on accessibility for people with auditory, cognitive, neurological, and visual impairments, ageing populations, and mobility for physical special needs. The book explores some of the overlaps between inclusive design and web accessibility to help managers, designers, developers, policy makers, and researchers optimize their efforts in these overlapping areas. Based on the AHFE 2016 International Conference on Design for Inclusion, held on July 27-31, 2016, in Walt Disney World®, Florida, USA, this book discusses new design technologies, highlighting various requirements of individuals within a community. Thanks to its multidisciplinary approach, the book represents a useful resource for readers with different kinds of backgrounds and provides them with a timely, practice-oriented guide to design for inclusion.